PENDEKATAN METODE NORDIC BODY MAP DALAM IDENTIFIKASI RISIKO ERGONOMI (STUDI: KASUS PERAWAT POLI RS X) - Nanta Sigit; Hermanus Alfonsus Ngara (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to determine the causes of the risk of musculoskeletal disorders (MSDs) in poly nurses at Hospital X. This is because the activities of poly nurses often use manual handling and repetitive motions as well as lifting or moving patients and pushing patient wheelchairs when providing health services so that this condition can cause muscle injuries in poly nurses. Referring to this problem, an analysis was conducted on all poly nurses at Hospital X. This study is an observational study with a cross-sectional design, with a total sample of 30 nurses. The research method used is an analytical method using the Nordic Body Map (NBM) questionnaire. The results of the NBM analysis provide information on changes in the distribution of musculoskeletal disorders (MSDs) complaint levels. Based on the results of the study of ergonomic risks due to musculoskeletal disorders in poly nurses from 30 questions in the questionnaire, the researchers took six points that are at risk of injury and can interfere with nurses' activities, namely the nape of the neck with a score of 1 (56%), 2 (37%) and 3 (7%), neck with a score of 1 (67%), 2 (27%), 3 (8%), left and right shoulders with a score of 1 (67%), 2 (30%) and 3 (3%), back with a score of 1 (54%), 2 (10%), 3 (33%), 4 (3%) and waist with a score (1 (47%), 2 (23%), 3 (27%), 4 (3%), and pelvis with a score of 1 (77%), 2 (13%), 3 (7%), 4 (3%), which means no pain (not feeling any disturbance in a particular part) with a score of 1, somewhat pain (feeling a little disturbance or pain in a particular part) with a score of 2, pain (feeling discomfort in certain parts of the body) with a score of 3, and very painful (feeling discomfort in certain parts on a high scale) with a score of 4.